Pyrogenic Carbon Lacks Long-Term Persistence in Temperate Arable Soils - Lutfalla, Suzanne; Abiven, Samuel; Barré, Pierre; Wiedemeier, Daniel B.; Christensen, Bent T.; Houot, Sabine; Kätterer, Thomas; Macdonald, Andy J.; van Oort, Folkert; Chenu, Claire (Frontiers in Earth Science, 2017)
Pyrogenic organic carbon (PyOC) derived from incomplete burning of biomass is considered the most persistent fraction of soil organic carbon (SOC), being expected to remain in soil for centuries. However, PyOC persistence has seldom been evaluated under field conditions. Based on a unique set of soils from five European long-term bare fallows, i.e. vegetation-free field experiments, we provide the first direct comparison between PyOC and SOC persistence in temperate arable soils. We found that soil PyOC contents decreased more rapidly than expected from current concepts, the mean residence time of native PyOC being just 1.6 times longer than that of SOC. At the oldest experimental site, 55% of the initial PyOC remained after 80 years of bare fallow. Our results suggest that while the potential for long-term C storage exists, the persistence of PyOC in soil may currently be overestimated.